Faktor-faktor yang Mempengaruhi Keputusan Kredit Pada UMKM di Kabupaten Banyumas Pada Masa Pandemi Covid-19 - Ade Noviana Azhar; Yusriati Nur Farida (Program Studi S1 Akuntansi Fakultas Ekonomi & Bisnis Univesitas Jenderal Soedirman, 2021)
This study aims to determine the effect of financial literacy, education level, credit procedures, and interest rates on credit decisions at MSMEs during the Covid-19 pandemic. The sampling technique used convenience sampling with a sample size of 100 MSME actors in Banyumas Regency. The data analysis technique used in the study was multiple linear regression analysis. The results showed that: (1) financial literacy has a positive and significant effect on credit decisions at MSMEs; (2) education level does not affect credit decisions at MSMEs; (3) credit procedures have a positive and significant effect on credit decisions at MSMEs; (4) interest rates do not affect credit decisions at MSMEs. The implication of this research is that understanding financial literacy is very helpful for MSME actors in determining credit decisions. Good financial literacy will affect a person's way of thinking about financial conditions and affect someone in making strategic decisions and good financial management. Ease of easy credit procedures will encourage MSMEs to make credit decisions. Businesses tend to prefer credit procedures that are quick, easy, and simple.